Complex and Dynamic Interactions between Parvovirus Capsids, Transferrin Receptors, and Antibodies Control Cell Infection and Host Range - Callaway, Heather M. (J Virol, 2018)
Antibody and receptor binding are key virus-host interactions that control host range and determine the success of infection. Canine and feline parvovirus capsids bind the transferrin receptor type 1 (TfR) to enter host cells, and specific structural interactions appear necessary to prepare the stable capsids for infection. Here, we define the details of binding, competition, and occupancy of wild-type and mutant parvovirus capsids with purified receptors and antibodies. TfR-capsid binding interactions depended on the TfR species and varied widely, with no direct relationship between binding affinity and infection. Capsids bound feline, raccoon, and black-backed jackal TfRs at high affinity but barely bound canine TfRs, which mediated infection efficiently. TfRs from different species also occupied capsids to different levels, with an estimated 1 to 2 feline TfRs but 12 black-backed jackal TfRs binding each capsid. Multiple alanine substitutions within loop 1 on the capsid surface reduced TfR binding but substitutions within loop 3 did not, suggesting that loop 1 directly engaged the TfR and loop 3 sterically affected that interaction. Binding and competition between different TfRs and/or antibodies showed complex relationships. Both antibodies 14 and E competed capsids off TfRs, but antibody E could also compete capsids off itself and antibody 14, likely by inducing capsid structural changes. In some cases, the initial TfR or antibody binding event affected subsequent TfR binding, suggesting that capsid structure changes occur after TfR or antibody binding and may impact infection. This shows that precise, host-specific TfR-capsid interactions, beyond simple attachment, are important for successful infection. IMPORTANCE Host receptor binding is a key step during viral infection and may control both infection and host range. In addition to binding, some viruses require specific interactions with host receptors in order to infect, and anti-capsid antibodies can potentially disrupt these interactions, leading to neutralization. Here, we examine the interactions between parvovirus capsids, the receptors from different hosts, and anti-capsid antibodies. We show that interactions between parvovirus capsids and host-specific TfRs vary in both affinity and in the numbers of receptors bound, with complex effects on infection. In addition, antibodies binding to two sites on the capsids had different effects on TfR-capsid binding. These experiments confirm that receptor and antibody binding to parvovirus capsids are complex processes, and the infection outcome is not determined simply by the affinity of attachment.